The paradoxical lean phenotype of hypothyroid mice is marked by increased adaptive thermogenesis in the skeletal muscle - Kaspari, Rachel; Reyna-Neyra, Andrea; Jung, Lara; Torres-Manzo, Alejandra Paola; Hirabara, Sandro M.; Carrasco, Nancy (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Obesity is a major health problem worldwide, given its growing incidence and its association with a variety of comorbidities. Weight gain results from an increase in energy intake without a concomitant increase in energy expenditure. To combat the obesity epidemic, many studies have focused on the pathways underlying satiety and hunger signaling, while other studies have concentrated on the mechanisms involved in energy expenditure, most notably adaptive thermogenesis. Hypothyroidism in humans is typically associated with a decreased basal metabolic rate, lower energy expenditure, and weight gain. However, hypothyroid mouse models have been reported to have a leaner phenotype than euthyroid controls. To elucidate the mechanism underlying this phenomenon, we used a drug-free mouse model of hypothyroidism: mice lacking the sodium/iodide symporter (NIS), the plasma membrane protein that mediates active iodide uptake in the thyroid. In addition to being leaner than euthyroid mice, owing in part to reduced food intake, these hypothyroid mice show signs of compensatory up-regulation of the skeletal-muscle adaptive thermogenic marker sarcolipin, with an associated increase in fatty acid oxidation (FAO). Neither catecholamines nor thyroid-stimulating hormone (TSH) are responsible for sarcolipin expression or FAO stimulation; rather, thyroid hormones are likely to negatively regulate both processes in skeletal muscle. Our findings indicate that hypothyroidism in mice results in a variety of metabolic changes, which collectively lead to a leaner phenotype. A deeper understanding of these changes may make it possible to develop new strategies against obesity.